Body balance maintenance ability estimation in artistic female gymnasts on various stages of sport advancement - Kruczkowski, D.; Supinska, A. (World Congress of Performance Analysis of Sport VIII, 2008)
One of the most important stimulation elements of human development, including movement development, is widely implied activity, as a feature that regulates human activity style. Also human biological development, stimulated by physical activity, accordingly to the intensity of the stimuli, gets a proper direction and dynamism in different ontogenesis stages. Long term researches under Hirtz (1985) supervision, regarding the training affects revealed in coordination motor ability level appointed on the training stimulation which significantly increases its estimation. In this work progressive improvement of body balance maintenance ability was noticed also in gymnasts group after age 14, which evidences about possibility of shaping this ability after sensitive period while developmental stabilization stage (Hirtz, Starosta 2001; Kruczkowski, Kucharska 2002; Starosta 2003). Statistic significant difference between the level of body balance maintenance ability of 7-10 years old gymnasts and the older group, measured using standard probe with eyes opened, is a result of developmental characteristic for coordination side of human motorics. Specific probe, after stimulation of balance centre with turn stimuli, appeared to be very informative for this sport discipline, appointing on statistic significant between youth, junior and senior athletes. It may suggest about multi-form of body balance maintenance ability and proper sensibility of neural-muscular apparatus on instant stimulation with training. Significant dispersion of the results around average value on each analysed stage appoint on huge individual variability in manifesting the analysed ability level which confirms significant participation of natural element.